2000
DOI: 10.1002/(sici)1097-4636(200008)51:2<200::aid-jbm8>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging time of sol on structure andin vitro calcium phosphate formation of sol-gel-derived titania films

Abstract: Titanium and its alloys have been used successfully in the manufacture of orthopedic and dental implants to replace damaged bone tissue. In this study, different sol-gel-derived TiO(2) coatings were produced on titanium substrates using different aging times (5, 10, 24, or 48 h) of the sol before dipping the coatings and varying numbers (one, three, or five) of coating layers. The influence of the aging time of the sol on the structure of the titania coatings with respect to in vitro bioactivity was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Substrate withdrawal speed, viscosity of precursor solution, viscous drag, gravitational force and liquid-vapor surface tension play a peculiar role in deciding the required coating thickness onto the substrate [40][41][42]. Dip coating involves dipping of sample in the precursor solution followed by constant speed linear withdrawal of sample to deposit thin coating.…”
Section: Dip Coatingsmentioning
confidence: 99%
“…Substrate withdrawal speed, viscosity of precursor solution, viscous drag, gravitational force and liquid-vapor surface tension play a peculiar role in deciding the required coating thickness onto the substrate [40][41][42]. Dip coating involves dipping of sample in the precursor solution followed by constant speed linear withdrawal of sample to deposit thin coating.…”
Section: Dip Coatingsmentioning
confidence: 99%
“…This also highlights the utility of thin ceramic coatings in implant applications where significant strain is applied to the implant. It is known that sol-gel-derived titania coatings attract calcium and phosphate from the body fluid and form bone-like calcium phosphate on the surface, thus promoting bone bonding [13,19,20]. In addition, sol-gel processing of a Ti alloy has been shown to promote increased attachment of osteoblasts and enhanced formation of mineralized matrix [21].…”
Section: Discussionmentioning
confidence: 99%
“…Titanium, as a biocompatible material, has been used to enhance implant incorporation in bone for dental, craniofacial, and orthopedic applications. Studies have demonstrated that nanoporous titanium dioxide (TiO 2 ) surface modification alters nanoscale topography improving soft tissue attachment on titanium implants surface [65,66]. For example, the uses of nanoporous TiO 2 surface-modified implants, in a human dental clinical study, showed that TiO 2 thin film increased adherence in early healing of the human oral mucosa and reduced marginal bone resorption [67].…”
Section: Applying Nanotechnology To Bone Reconstructionmentioning
confidence: 99%